The Measures of Sustainable Development – a Study Based on the European Monitoring of Energy-related Indicators - Żelazna, Agnieszka; Gołębiowska, Justyna (Problemy Ekorozwoju, 2015)
Sustainable socio-economic development is the guiding principle in the European Union policy. The implementation of that principle is monitored by a set of indicators being developed since 1995, referred to as the indicators of sustainable development. The monitoring is conducted both at the level of Member State, as well as of the entire community. The main indicators describing the social, economic and environmental issues of the EU functioning show positive results in regard to the implementation of the sustainable development strategy; however, in the themes related to the issues of social inclusion, sustainable transport, and global partnership, the indicators show a negative trend. In this paper, the sustainable development indicators in the theme of Climate change and energy are described and analyzed in detail. Their changes over the last decades were strongly stimulated by the EU energy policy. In connection with the implementation of numerous programs for the promotion of renewable energy sources, their share in the energy market is growing, whereas the greenhouse gas emissions from the EU area and the primary energy consumption are falling. During the last 25 years, the total man-made GHG emission in the EU was reduced by 18%. It should be noted that these changes are influenced not only by the manner of energy management stimulation in the EU, but also by an equally significant problem of the economic crisis, geopolitical situation, and the resulting economic change. Moreover, some indicators relevant to the concerned theme, such as energy dependency, clearly show a negative trend.